Endometriosis and dysbiosis: State of art - Zizolfi, Brunella; Foreste, Virginia; Gallo, Alessandra; Martone, Simona; Giampaolino, Peirluigi; Di Spiezio Sardo, Attilio (Frontiers in Endocrinology, 2023)
Endometriosis is a complex and heterogeneous disease affecting approximately 10% of reproductive age women. The hypothesis that alterations in the microbiota are involved in the pathogenesis of endometriosis has been postulated. Possible explanations for the implications of dysbiosis in endometriosis include the Bacterial Contamination hypotesis and immune activation, cytokine-impaired gut function, altered estrogen metabolism and signaling. Thus, dysbiosis, disrupt normal immune function, leading to the elevation of proinflammatory cytokines, compromised immunosurveillance and altered immune cell profiles, all of which may contribute to the pathogenesis of endometriosis. The aim of this review is to summarize the available literature data about the relationship between microbiota and endometriosis.